A practical approach on radioprotection in the treatment of radioiodine for thyroid cancer (Brazilian Journal of Radiation Sciences (BJRS), 2018)
There are several protocols for the treatment and follow-up of differentiated thyroid cancer. All of them gather evidence on the evolution and treatment and try to establish a treatment standard. However, there are few occasions in which this issue is addressed from the standpoint of radiological protection, as the ICRP 94 and TECDOC 1608. The focus of our work is to demonstrate that simple actions in the routine of workers in the Nuclear Medicine Service interfere positively in the radiation protection of all those involved in the patient's care, also optimizing their well being during the procedure. In the current model, the patient participates in an interview with nurses, doctors and physicists, before admission, and receives written and verbal information about the treatment procedures in order to diminish his anxiety and clarify possible doubts. In all the cases under hospital care there were no instances of high exposure (above 1mSv/month or 6 mSv/year) among the staff. With the participation of all involved, there was an escalating improvement in the reduction of complications generated by the patient’s anxiety, waste decrease, providing better comfort during hospital care) and minimization of occupational hazard affecting the staff in charge of the patient’s room maintenance after hospital leave.